2007
DOI: 10.4315/0362-028x-70.9.2199
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks Where Food Workers Have Been Implicated in the Spread of Foodborne Disease. Part 3. Factors Contributing to Outbreaks and Description of Outbreak Categories

Abstract: In this article, the third in a series of several reviewing the role of food workers in 816 foodborne outbreaks, factors contributing to outbreaks and descriptions of different categories of worker involvement are discussed. All the outbreaks had worker involvement of some kind, and the majority of food workers were infected. The most frequently reported factor associated with the involvement of the infected worker was bare hand contact with the food followed by failure to properly wash hands, inadequate clean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(142 citation statements)
references
References 19 publications
3
129
0
10
Order By: Relevance
“…Meat could be contaminated from cutting boards [17]; other ingredients could be contaminated from the hands of food handlers [18]. Furthermore, seasoning sauces and mayonnaise used in sandwich dressing could also be contaminated.…”
Section: Discussionmentioning
confidence: 99%
“…Meat could be contaminated from cutting boards [17]; other ingredients could be contaminated from the hands of food handlers [18]. Furthermore, seasoning sauces and mayonnaise used in sandwich dressing could also be contaminated.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the serving utensils were carelessly kept on the bare floor of the serving area at the time of serving, and back into the ready-to-eat food when the need arises without washing. Similarly, several risk factors related to the food service environment contribute to occurrence of foodborne illness: poor personal hygiene, inadequate sanitization of surfaces or equipment, cross contamination of prepared food with contaminated ingredients and inadequate temperature control [73,74]. Food handling personnel play important role in ensuring food safety throughout the chain of food production, processing, storage and preparation.…”
Section: Microbiological Safety Of Cooked Food Samplesmentioning
confidence: 99%
“…Food handlers may also shed food borne pathogens as E.coli and non typhoidal salmonella during the infectiousness period or during the recovery period of a gastrointestinal sickness (Adams and Moss, 2008). Todd et al (2007) formed a workgroup and analyzed 816 food borne outbreaks where food workers have been implicated in the spread of food borne diseases. In their last publication, they found that the most frequently reported food worker errors were handling of food by a person either actively infected by or carrying a pathogen bare-hand contact with food, failure to properly wash hands when necessary, insufficient cleaning of processing or preparation equipment or kitchen tools.…”
Section: Introductionmentioning
confidence: 99%